Pelatihan Pembuatan Materi Pengajaran dan Penggunaan Aplikasi Perpustakaan bagi Guru SMP Swadaya Karya Cibuni Desa Indragiri Bandung - Loekito, Jimmy Agustian; Wijaya, Marvin Chandra; Tjiharjadi, Semuil; Lehman, Andrew Sebastian; Tanubrata, Markus; Wong, Hendry; Yapinus, Pin Panji; Chandra, Jonathan; Pranata, Yosafat Aji; Setiawan, Deni; Hutasoit, Aldi Febri (Universitas Nusantara PGRI Kediri, 2023)
Swadaya Karya Cibuni Junior High School, Indragiri Village, Bandung Regency, feels the need for a better learning system. One of them is the creation of learning materials that can be used online and offline. Therefore, it will be taught how to make teaching materials using PowerPoint accompanied by videos. Apart from that, it is necessary to use computer applications to make the process of borrowing books in the SMP Swadaya Karya Cibuni library more well-organized. The method used in this training is a direct training system in schools. Maranatha Christian University prepared the training materials and also created a library application that Swadaya Karya Middle School can use. Training is given to teachers at Swadaya Karya Junior High School directly at school. The results of this training were considered suitable by the training participants based on the survey results. The training participants felt that the materials for making these teaching materials were beneficial. In addition, the participants also thought that the library application was easy to use and very useful.